(untitled) (American Journal of Islam and Society, 2009)
The practice of charity, which is commonly voluntary by definition, is embedded within religious institutions or communities to support their vision of social welfare. In this book, Egbert Harmsen underlines some improvements, advantages, and weaknesses as well as varieties of the roles played by Muslim-based voluntary organizations in the Middle East in general, and in Jordan in particular. He reexamines whether such civic values as voluntary, autonomous, egalitarian, community-based initiatives, self-reliance, and independence under which civil society organizations developed can impact Muslim society on a larger scope. The author reassesses previous research findings, particularly those presented by such observers as Janine Clark and Sami Zubaida. Clark’s observation of (horizontal) networks embedded among middle-class Muslims reveal that the lower class (the poor) does not benefit very much from the existing social institutions. Meanwhile, Zubaida’s scrutiny of the (vertical) relation between Muslim associations and their needy clients shows that the resulting relationships are generally paternalistic. In response to Clark’s argument, Harmsen points out that while the social institutions set up by the middle class do serve middle-class families, they by no means ...